أهمیة تنمیة كفاءات الموارد البشریة بالنسبة للمنظمات -دراسة حالة مستشفى الإخوة مغلاوي بمیلة - حیمر حمودي (Finance and Business Economies Review, 2017)
Human resources are concerned with the attention of organizations, because they ensure their continuity and success, therefore they strive to maintain high levels of competencies in their human resources, so that they can adapt to rapid environmental changes. For this reason they needs to developing competencies, which is the subject of our research, under the title: The importance of human resources competencies development for the organizations - a study of the state of the public hospital organization Brothers Meghlawi Mila. At the end of the study, we concluded that the development of competencies is of great importance to the organizations and that they are a necessity to meet their future challenges. However, we noted the absence of this proposal in the field hospital, where we found that most of the human resources working in the administration did not benefit from any program to develop competencies. Which they are not commensurate with their experience or their functional levels